Analisis Nilai CBR Dan Permeabilitas Tanah Lempung Yang Distabilisasi Dengan Fertilizer Di Desa Alam Buana Kabupaten Luwu Timur - Susetyo, Agus Hary; Sariman, Syahrul; Yunianti, Nur Hadijah (Program Studi Teknik Sipil Universitas Bosowa, 2024)
In general, clayey soil has low bearing capacity; therefore, clayey soil needs to be improved in terms of its bearing capacity before constructing anything on it. This research aims to utilize fertilizer to enhance the CBR (California Bearing Ratio) and reduce the permeability of clayey soil. One way to improve clayey soil is by incorporating fertilizer as a soil stabilization material, by conducting CBR and Permeability Tests. Urea fertilizer readily dissolves in water and exhibits easy water absorption properties (hygroscopic). On the other hand, NPK fertilizer is a compound fertilizer containing nitrogen (N), phosphorus (P), and potassium (K) in varying compositions, with each element represented by the initial letter of its name (N, P, and K). In this study, 10% Urea is added to the soil, and there is variation in the amount of NPK, namely 0%, 5%, 10%, and 15%. The research results indicate that with the addition of NPK fertilizer, the CBR value continues to increase compared to the original soil and soil with only urea mixture. Meanwhile, in the Permeability Test, with each addition of NPK fertilizer, the coefficient of permeability value experiences a decrease.